Level of Trust, Knowledge and Religiosity Against Muzakki's Interest in Issuing Zakat at BAZNAS Salatiga City - Heru Prastyo; Tri Yunianto; Rugaya Renwarin (GoAcademica Research & Publishing, 2021)
This research aim to to know: (1) Influence level trust to enthusiasm of Muzakki in releasing religious obligatory, (2) Knowledge to enthusiasm of Muzakki in releasing religious obligatory, (3) Religiusitas to enthusiasm of Muzakki in releasing religious obligatory, (4) Influence between level trust, and knowledge of religiusitas to enthusiasm of Muzakki in releasing religious obligatory in BAZNAS Town of Salatiga. Type Research which is used in this thesis is research of combination (methods mixed) between quantitative diskripsi and diskripsi qualitative. Determination of sampel use method of purposive sampling. Sampel obtained by counted 80 responder of muzakki which paying religious obligatory in BAZNAS Salatiga. Pursuant to result of research in Body of Amil Religious Obligatory National (BAZNAS) Town of Salatiga indicate that: Trust storey;level have an effect on positive and signifikan to enthusiasm of muzakki, Knowledge have an effect on positive and signifikan to enthusiasm of muzakki, Religiusitas have an effect on positive and signifikan to enthusiasm of muzakki, and Storey;Level trust, and knowledge of religiusitas by together influence by signifikan enthusiasm variable of muzakki in [Releasing] Religious obligatory in Body of Amil Religious Obligatory National (Baznas) Town of Salatiga.